2001
DOI: 10.1111/j.1348-0421.2001.tb02616.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection Method of Clostridium scindens and C. hiranonis in Human Fecal Samples

Abstract: Clostridium scindens and C. hiranonis have high bile acid 7a-dehydroxylating activity. Direct PCR and nested PCR with the specific primers for C. scindens and C. hiranonis were developed and tested for the detection of them in human fecal samples. Nested PCR detected C. scindens in all samples, but direct PCR detected it in 27 of 34 samples. Regarding C. hiranonis, nested PCR detected it in only 18 of 34 samples although nested PCR has a high level of sensitivity. Nested PCR was a specific and sensitive method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…, Streptococcus spp. , E. coli, Blautia spp., Fusobacterium spp., Clostridium Hiranonis )33 in the fecal microbiota were analyzed by qPCR assays, as described previously for canine fecal samples 18, 34…”
Section: Methodsmentioning
confidence: 99%
“…, Streptococcus spp. , E. coli, Blautia spp., Fusobacterium spp., Clostridium Hiranonis )33 in the fecal microbiota were analyzed by qPCR assays, as described previously for canine fecal samples 18, 34…”
Section: Methodsmentioning
confidence: 99%
“…Early molecular studies showed that C. scindens and Eg. lenta, which both belong to the functional group of biliary steroid-metabolising bacteria, are common members of the human intestinal microbiota (Bokkenheuser et al, 1979;Doerner et al, 1997;Schwiertz et al, 2000;Kitahara et al, 2001). Besides, as in the case of SECO demethylation by P. productus, the dehydroxylation activity was observed for several strains of Eg.…”
Section: Identification Of Seco-dehydroxylating Bacteriamentioning
confidence: 99%
“…scindens is an indigenous bacteria in human intestine (18) and has high activity compared to other bile acid 7α-dehydroxylating bacteria (5, 16), it follows from these results that C. scindens might be the most important species in bile acid 7α-dehydroxylation.…”
Section: Quantification Of C Scindensmentioning
confidence: 67%
“…Species-specific primers for C. scindens were used as previously described (18). Realtime PCR was performed with the LightCycler TM system (Roche Molecular Biochemicals, Mannheim, Germany) and the double-stranded DNA binding dye SYBR ® Green I (Roche Molecular Biochemicals) according to Sakamoto et al (23).…”
Section: Bacterial Strain C Scindens Jcm 6567mentioning
confidence: 99%
See 1 more Smart Citation